Role of adrenomedullin2/ intermedin in pregnancy induced vascular and metabolic adaptation in mice - Yallampalli, Chandra; Betancourt, Ancizar; Mishra, Akansha; Pennington, Kathleen A.; Ruano, Simone Hernandez; Tacam, Moises; Chauhan, Madhu (Frontiers in Physiology, 2023)
Introduction: Adrenomedullin2 (AM2) shares its receptor with Calcitonin gene related peptide and adrenomedullin with overlapping but distinct biological functions. Goal of this study was to assess the specific role of Adrenomedullin2 (AM2) in pregnancy induced vascular and metabolic adaptation using AM2 knockout mice (AM2−/−). Method: The AM2−/− mice were successfully generated using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Nuclease Cas nine system. Phenotype of pregnant AM2−/− mice was assessed with respect to its fertility, blood pressure regulation, vascular health and metabolic adaptations and compared to the wild type littermates (AM2+/+). Results: Current data shows that AM2−/− females are fertile with no significant difference in number of pups/litter compared to the AM2+/+. However, ablation of AM2 decreases the gestational length and the total number of pups born dead or that die after birth is greater in AM2−/− mice compared to AM2+/+ mice (p < 0.05). Further AM2−/− mice exhibit elevated blood pressure and elevated vascular sensitivity for the contractile responses to angiotensin two and higher serum sFLT-1 trigylcerides levels compared to AM2+/+(p < 0.05). In addition, AM2−/− mice develop glucose intolerance with elevated serum levels of Insulin during pregnancy compared to the AM2+/+mice. Discussion: Current data suggests a physiological role for AM2 in pregnancy induced vascular and metabolic adaptations in mice.